Real Time CO Gas Monitoring System Using ESP8266 and Telegram: Sistem Pemantauan Gas CO Secara Real-Time Menggunakan ESP8266 dan Telegram - Rony Setiawan; Izza Anshory (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Carbon monoxide (CO) is a toxic gas that cannot be detected by human senses and poses significant health risks in indoor environments. Specific Background Increasing air pollution and limited awareness highlight the need for real-time monitoring systems capable of detecting hazardous gas concentrations. Knowledge Gap Previous monitoring systems were limited by the lack of IoT integration and real-time notification features for users. Aims This study aims to design and implement an IoT-based monitoring system for detecting CO gas levels using ESP8266 integrated with Telegram notifications. Results The system utilizes an MQ-7 sensor to measure CO concentration and successfully transmits data to users, showing stable readings between 10.54 PPM and 20.24 PPM, with automatic alerts triggered when levels exceed 20 PPM, activating buzzer and fan responses. Novelty The integration of MQ-7 sensor, ESP8266, and Telegram enables real-time monitoring and automated alert mechanisms in a single system. Implications This system provides a practical solution for indoor air quality monitoring and supports early detection of hazardous gas exposure to reduce health risks. Keywords: Carbon Monoxide, Internet of Things, MQ-7 Sensor, ESP8266, Air Quality Monitoring Key Findings Highlights System detects hazardous gas threshold and triggers automated warning devices Data transmission to users occurs instantly through messaging platform Sensor readings remain stable under normal environmental conditions